The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/cvi.13.2.239-245.2006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Immunity-Related Gene Expression in Small Intestines of Mice by Oral Administration of Lactoferrin

Abstract: Oral administration of lactoferrin (LF), an antimicrobial and immunomodulatory protein, shows a protective effect against infectious diseases, possibly via immunomodulation of the host. Initially, we confirmed an immunomodulatory effect of LF by observing changes in the number of cells in the leukocyte subsets in the peripheral blood and spleens of mice 1 day after oral administration of LF. Then we developed a quantitative reverse transcription-PCR method for 20 immunity-related genes of antimicrobial protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 38 publications
1
35
0
1
Order By: Relevance
“…Lactoferrin has the potential to promote development of both T H 1 and T H 2 immune responses, depending on experimental conditions [29,30]. Towards its utility as an adjuvant, in vivo and in vitro studies indicate that lactoferrin can increase relative production of IL-12 while decreasing IL-10, a negative regulator of IL-12 [19,[31][32][33]. Of critical importance, bovine lactoferrin added to murine macrophages infected with BCG enhanced the production of IL-12 relative to amounts of IL-10 [34].…”
Section: Introductionmentioning
confidence: 99%
“…Lactoferrin has the potential to promote development of both T H 1 and T H 2 immune responses, depending on experimental conditions [29,30]. Towards its utility as an adjuvant, in vivo and in vitro studies indicate that lactoferrin can increase relative production of IL-12 while decreasing IL-10, a negative regulator of IL-12 [19,[31][32][33]. Of critical importance, bovine lactoferrin added to murine macrophages infected with BCG enhanced the production of IL-12 relative to amounts of IL-10 [34].…”
Section: Introductionmentioning
confidence: 99%
“…Lactoferrin possesses a wide range of immunomodulatory activities [17][18][19] [20] [21] including promotion of the T-cell dominated DTH response towards BCG antigens [22,23], The ability of lactoferrin to enhance the generation of antigen specific DTH responses suggests that lactoferrin could promote development of specific T-cell responses against a complex antigen, such as BCG [24,25] The development of T-cell helper type 1 (T H 1) immunity is, in part, regulated by production of IL-12 [26,27]. A variety of in vivo studies have shown lactoferrin capable of increasing production of IL-12 [28][29][30]. IL-12 is clearly a critical component involved in directing T H 1 development effective in promoting protective host responses during MTB infection [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a high IL-12:IL-10 ratio from activated macrophages is indicative of a cytokine environment that is favored towards promotion of T H 1 immunity. A limited number of studies have shown increasing IL-12 with concurrent decrease of IL-10 levels following administration of Lactoferrin [44,46,47]. Lactoferrin also demonstrated direct in vivo stimulatory activity in naïve mice with recovered peritoneal cells from mice injected with Lactoferrin exhibiting increased in TNF-α, IL-6, and IL-12 production [1].…”
Section: Introductionmentioning
confidence: 99%